Penerapan Aplikasi Srikandi ( Sistem Kearsipan Dinamis Terintegrasi) Di Dinas Perpustakaan Dan Kearsipan Kabupaten Madiun: Implementation of the SRIKANDI Application (Integrated Dynamic Archival System) at the Department of Libraries and Archives - masud, masud ady saputro (Universitas Merdeka Madiun, 2025)
The development of technology and information is currently very rapid and has penetrated various fields of life. The utilization of technology and information in the field of government itself includes the use of the Integrated Dynamic Archival System (Srikandi) application. As a government unit, the Library and Archives Office of Madiun Regency also implements the SRIKANDI application in its administrative activities. This research explains how the use of technology and information, specifically the utilization of the Integrated Dynamic Archival System (Srikandi), is implemented at the Library and Archives Office of Madiun Regency. This study uses a qualitative research method, employing interviews and observations as tools to collect research data. The results of this study show that the utilization of the SRIKANDI application is carried out in every administrative activity, starting from the creation, storage, distribution, maintenance, and disposition of archives. In the process of creating outgoing letters, the Library and Archives Office of Madiun Regency uses the SRIKANDI application directly. The storage process for both incoming and outgoing letters is carried out using two methods: storing letters through the SRIKANDI application and manually. In the distribution process of outgoing letters, the Library and Archives Office of Madiun Regency uses the SRIKANDI application and WhatsApp. Furthermore, in the archive maintenance process, the Library and Archives Office of Madiun Regency does not yet have a system or flow for archiving because all archives have been entered into the National Data Center (PDN). In the disposition process, the Library and Archives Office of Madiun Regency conducts it directly using the SRIKANDI application. However, there are some obstacles in its implementation, including data loss, uneven application of the SRIKANDI application, and the absence of data backups.